BRIDGING THE PAST AND PRESENT: AN ANALYSIS OF SULTAN ZAINUL ABIDIN'S LEGACY THROUGH THE ZAINGAIR CANAL IN KASHMIR - Ishfaq Ahmad Mir (Journal of Accounting Research, Utility Finance and Digital Assets, 2023)
Sultan Zainul Abidin, popularly known as "Budshah," was a 15th-century ruler of Kashmir who left a lasting impact on the region's socio-economic landscape. Among his many contributions, the Zaingair Canal, which he commissioned for irrigation and transportation purposes, stands out as a significant feat of engineering. Despite its historical importance, the canal's legacy has been largely forgotten in modern-day Kashmir. This research paper aims to bridge the gap between the past and present by analyzing the impact of Sultan Zainul Abidin's legacy through the Zaingair Canal. Through a comprehensive review of historical texts, as well as fieldwork conducted in the Zaingair area, this paper will explore the canal's significance in the context of Kashmir's development, and shed light on its potential for revitalization in the present day.